A macro- and micromorphological survey of floral and extrafloral nectaries in the epiphytic cactus Rhipsalis teres (Cactoideae: Rhipsalideae) - Garcia de Almeida, Odair Jose [UNESP]; Paoli, Adelita Aparecida Sartori [UNESP]; Cota-Sanchez, J. Hugo (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Floral and extrafloral nectaries in plants favor pollination and defense against herbivory. Despite their wide distribution in plants and differences in position, structure, and topography, their biological and systematic significance has been underutilized. This study investigated the macro- and micromorphology of floral and extrafloral nectaries in the epiphytic cactus Rhipsalis teres and reports unusual bristle-like structures (bracteoles) functioning as extrafloral nectaries in the cactus family. The floral nectary is disc-shaped embedded in the hypanthial floral cup with anomocytic stomata as secreting structures present on the epidermal nectarial tissue. Small multicellular bristle-like extrafloral nectar-secreting structures, homologues to bracts, were observed on the plants stems and function as bracteolar nectaries having a relatively long and continuous secretory activity throughout several stages of the reproductive structures. Both the floral and bracteolar nectaries are functional. It is possible that in the latter nectar discharge occurs though epidermal cells, which build up pressure inside as nectar accumulates, thereby ending with rupture of the cuticle to release the liquid. The nectar in both secreting structures is scentless and colorless, and the concentration from floral nectaries is slightly lower than that of the bracteolar nectaries, 70.6% and 76.4%, respectively. The relatively higher concentration in the latter might be correlated with exposure, relative humidity and water evaporation, leading to crystallization of sugars on the stem surface in a short period of time. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Bracteolar nectary; Cactaceae; Floral nectary; Nectary disc; Nectar concentration; Rhipsalis teres